Optical analysis of various reflectors applied in solar beam down tower - Khlief, A.K. (Asian Research Publishing Network, 2016)
The concept of the reflective solar tower is based on the reflection of the solar radiations from heliostats toward reflective mirror at the top of the tower and then redirected the radiation to one of its foci on the ground. This new arrangement would allow setup the energy collection at the ground level; hence the heavy tower top setup is avoided. For the suggested beam down solar tower located at Universiti Teknologi Petronas, three reflective shapes are examined, i.e. ellipsoidal/concave, hyperboloid/convex and a flat surface. A comparative study is carried out using lightXlab simulation platform to investigate the effect of focal point distance on the radiation spread at the ground level and the effect of angle change of the second reflector on the radiation concentration as well as the beam travel. The results of the simulation showed that the flat surface reflector is having superiority and better control over the other two reflectors, in terms of beam concentration and beam travel. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.